Rencana Pengembalian Fungsi (Revitalisasi) Terminal Selindung Kota Pangkal Pinang sebagai Pusat Aktivitas Ekonomi, Sosial Dan Mobilitas Urban Yang Berkelanjutan - Rahmadan, Alyyah; Aqil Albajili, Hanif; Anjarsari, Nadia; Samsuddin, M. Afdal (Teewan Journal Solutions, 2025)
This research examines the revitalization plan for Terminal Selindung in Pangkalpinang City as an effort to optimize its function as a center for economic activities, social interactions, and sustainable urban mobility. Terminal Selindung, located on Komala Street, Selindung Baru Village, Gabek District, currently faces various problems such as infrastructure damage, lack of maintenance, and low utilization by the community. This study employs a quantitative descriptive method with financial feasibility analysis including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The analysis shows that the revitalization project requires Rp 1,161,562,000 with a completion time of 1 month and 5 days. NPV calculations at interest rates of 10% and 15% yield values of Rp 1,232,826,145 and Rp 962,491,711 respectively, with an IRR of 12.8%, BCR of 2.06, and Payback Period of 1.85 years. These results indicate that the Terminal Selindung revitalization project is financially feasible. The revitalization is expected to reduce traffic congestion, increase public transportation usage, and stimulate economic activities around the terminal.